HISTORICAL VIEWS AND DEVELOPMENT OF UZBEK NATIONAL GAMES (Academicia Globe: Inderscience Research, 2022)
The article discusses the origin of uzbek games of folk and their historical forms, as well as how they are expressed in folklore and classical literature. Information was provided on the types of games, seasonal games and groups of children's games. The lexical meaning of the word game was analyzed using a glossary and other dictionaries. Information was provided on the role of folk games in the life and culture of the nation.